Mapping Sensory Spots for Moderate Temperatures on the Back of Hand - Fan Yang; Guixu Chen; Sikai Zhou; Danhong Han; Jingjing Xu; Shengyong Xu (Sensors, 2017)
Thermosensation with thermoreceptors plays an important role in maintaining body temperature at an optimal state and avoiding potential damage caused by harmful hot or cold environmental temperatures. In this work, the locations of sensory spots for sensing moderate temperatures of 40–50 °C on the back of the hands of young Chinese people were mapped in a blind-test manner with a thermal probe of 1.0 mm spatial resolution. The number of sensory spots increased along with the testing temperature; however, the surface density of sensory spots was remarkably lower than those reported previously. The locations of the spots were irregularly distributed and subject-dependent. Even for the same subject, the number and location of sensory spots were unbalanced and asymmetric between the left and right hands. The results may offer valuable information for designing artificial electronic skin and wearable devices, as well as for clinical applications.